A deep-ultraviolet Raman and Fluorescence spectral library of 62 minerals for the SHERLOC instrument onboard Mars 2020. (December 2021) - Razzell Hollis, Joseph; Abbey, William; Beegle, Luther W.; Bhartia, Rohit; Ehlmann, Bethany L.; Miura, Jasper; Monacelli, Brian; Moore, Kelsey; Nordman, Austin; Scheller, Eva; Uckert, Kyle; Wu, Yen-Hung
Abstract: We report deep-ultraviolet (DUV) Raman spectra as measured by a SHERLOC analog instrument (248.6 ​nm excitation) for 92 samples representing 62 distinct minerals, including borates, carbonates, sulfates, phosphates, halides, metal oxides & hydroxides, silicates & phyllosilicates. We found that DUV Raman is capable of detecting the majority of these minerals, with major mineral peaks occurring at ∼500, ∼850, 950–1200, and ∼3600 ​cm −1, and that detection thresholds will be better for the SHERLOC flight instrument than the analog used in this study. Minerals can be classified (e.g., sulfate vs carbonate, or pyroxene vs olivine) based on the number of major peaks and their general positions. Identification of specific mineral phases is possible based on precise Raman peak positions, provided the difference between spectrally similar minerals is at least 10 ​cm −1 to overcome the estimated instrumental uncertainty of ±5 ​cm −1 for all peak positions reported in this study. A number of silicate minerals did not produce measurable Raman signal, and iron-rich minerals tend to be more difficult to detect due to significant UV absorption. Many Mars-relevant minerals expected to occur in Jezero crater should be detectable to SHERLOC even during short-exposure survey scans. This library will help inform the detection and identification of mineral phases in Martian samples using the SHERLOC instrument onboard the Mars 2020 Perseverance rover. Highlights: We used a SHERLOC analog instrument to build a DUV Raman library of minerals. Many minerals relevant to Jezero Crater on Mars can be detected by SHERLOC. Most minerals can be classified (carbonates, sulfates, etc) by their spectra. Identifying specific minerals is possible, if peak positions are distinct enough. This library will help us identify minerals on Mars using the SHERLOC instrument.